A Vulnerable System: The History of Information Security in the Computer Age by Andrew Stewart (review). - Slayton, Rebecca (Technology & Culture, 2023)
I A Vulnerable System i challenges this obsession, showing that many of the vulnerabilities that concern security practitioners today have a much longer history. Stewart also states that the crash would "shift the focus from short-termism back to fundamentals" (p. 77), thereby pivoting to the next chapter's discussion of Microsoft's security program. Chapter 4 discusses internet vulnerabilities and products that emerged during the dot-com boom of the late 1990s and highlights a "lucrative feedback loop", wherein hackers exposed vulnerabilities and then were paid to help fix those vulnerabilities.